Paracetamol degradation intermediates and toxicity during photo-Fenton treatment using different iron species - Trovo, Alam G. [UNESP]; Pupo Nogueira, Raquel F. [UNESP]; Agueera, Ana; Fernandez-Alba, Amadeo R.; Malato, Sixto (Pergamon-Elsevier B.V. Ltd, 2012)
The photo-Fenton degradation of paracetamol (PCT) was evaluated using FeSO4 and the iron complex potassium ferrioxalate (FeOx) as iron source under simulated solar light. The efficiency of the degradation process was evaluated considering the decay of PCT and total organic carbon concentration and the generation of carboxylic acids, ammonium and nitrate, expressed as total nitrogen. The results showed that the degradation was favored in the presence of FeSO4 in relation to FeOx. The higher concentration of hydroxylated intermediates generated in the presence of FeSO4 in relation to FeOx probably enhanced the reduction of Fe(III) to Fe(II) improving the degradation efficiency. The degradation products were determined using liquid chromatography electrospray time-of-flight mass spectrometry. Although at different concentrations, the same intermediates were generated using either FeSO4 or FeOx, which were mainly products of hydroxylation reactions and acetamide. The toxicity of the sample for Vibrio fischeri and Daphnia magna decreased from 100% to less than 40% during photo-Fenton treatment in the presence of both iron species, except for D. magna in the presence of FeOx due to the toxicity of oxalate to this organism. The considerable decrease of the sample toxicity during photo-Fenton treatment using FeSO4 indicates a safe application of the process for the removal of this pharmaceutical. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Pharmaceuticals; Photodegradation; Solar; LC-TOF-MS; Wastewater